Evaluasi Pengelolaan Keuangan Pesantren Melalui Implementasi Aplikasi Simkeu di Pesantren Api Syubbanul Wathon Tegalrejo Secang - Nala Khilmi; Siswanto; Laili Syarifa (Program Studi Manajemen Pendidikan, 2024)
This study aims to evaluate the financial management of API Syubbanul Wathon Tegalrejo Secang Islamic Boarding School through the implementation of the Financial Management Information System (SIMKEU) application. The background of this research is that the challenges in financial recording that are still done manually, prone to errors, and take a long time. The research method used uses a case study approach with a qualitative approach. Data was collected through in-depth interviews with pesantren leaders and administrative staff, direct observation of the financial management process, and analysis of documents related to pesantren finance. The research was carried out at API Syubbanul Wathon Tegalrejo Secang Islamic Boarding School over a certain period. The results showed that the implementation of SIMKEU succeeded in increasing efficiency in recording and financial management by reducing the time required for the transaction recording process and improving the accuracy of financial statements. However, the study also identified several challenges, such as issues with information and communication technology infrastructure that need to be improvement, and the initial adaptation phase requiring extra time and effort from pesantren staff. Based on the study’s results, it is recommended to enhance information and communication technology infrastructure, and increase training for pesantren staff to maximize the benefits of SIMKEU implementation in the future. In conclusion, the implementation of SIMKEU at API Syubbanul Wathon Tegalrejo Secang Islamic Boarding School has made a significant contribution in improving the efficiency and transparency of Islamic boarding school financial management. This study provides practical guidance for other pesantren that want to adopt similar technologies in an effort to improve financial management effectively and efficiently.